Impact of storage and processing on vitamin c in fresh vegetables - Amalia, Nirmala; Afifah, Suci Nur; Hidayat, Atmajaya Nur; Setiawan, Wayan; Budiarti, Erri Erlita; Maerani, Maerani; Faturochman, Hadi Yusuf (Program Studi Gizi, 2025)
Vitamin C is a vitamin that is susceptible to oxidation, so it easily deteriorates when exposed to heat, light, or high temperatures. The purpose of this article is to summarize existing information on various storage and processing techniques related to vitamin C content, particularly fresh vegetables.The effect of temperature on vitamin C storage showed variations in the percentage of vitamin C content stored at room temperature (28°C-35°C) and low temperature (5°C-15°C). At low temperatures, the percentage of vitamin C content is higher than at room temperature. Storage at too high a temperature can reduce vitamin C content at the extreme temperature of 48°C. In addition, cold storage is a solution by freezing fresh vegetables so that in addition to maintaining the respiration rate, it also maintains the quality of vegetables from microorganisms. Therefore, steam blanching treatment before freezing will reduce the vitamin C compounds contained because it affects vitamin C which is very easily oxidized.